The Value Orientation of Multicultural Islamic Education in the Sipakatau Culture - Muhammad Tang; Yaqub Cikusin; Djunaedy Ghony (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2018)
The purpose of this study was to interpret and describe the values ​​of the culture of Sipakatau in the Bugis community to become the foundation for the development of Multicultural Islamic education. The research approach used is qualitative-ethnographic research developed by Gay, Mills, Aurasian & Creswell. Data collection techniques used are in the form of observations, interviews, and documents. Then the data analysis used is a model developed by Miles & Hubermen. After conducting research, it was shown that the cultural values ​​of Sipakatau in Bugis communities in Barang village could be the basis for the development of Multicultural Islamic Education, namely with the concept of